2021
DOI: 10.1186/s40337-021-00408-6
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative status in plasma, urine and saliva of girls with anorexia nervosa and healthy controls: a cross-sectional study

Abstract: Background Anorexia nervosa (AN) is a serious psychosomatic disorder with unclear pathomechanisms. Metabolic dysregulation is associated with disruption of redox homeostasis that might play a pivotal role in the development of AN. The aim of our study was to assess oxidative status and carbonyl stress in plasma, urine and saliva of patients with AN and healthy controls. Methods Plasma, spot urine, and saliva were collected from 111 girls with AN (a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…The GSH/GSSG ratio was estimated according to the recently described method by Kovalčíková et al [ 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…The GSH/GSSG ratio was estimated according to the recently described method by Kovalčíková et al [ 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…(11) Several studies showed that AN is associated with increased oxidative stress markers, with a decrease in these markers after weight gain. (21,22) Thus, this mechanism should be considered when formulating a hypothesis for the increase of ferritin in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the level of AGEs in the renal cortex was highest in the ZL rats that exhibited the lowest body weight. It was shown that AGEs are lipophilic and, thus, are preferentially stored in the fat tissue [ 25 ]. In the case of lower body fat content (typical of ZL rats in our experiment), AGEs could be stored in higher amounts in other tissues, e.g., in the renal cortex, as suggested by this study.…”
Section: Discussionmentioning
confidence: 99%